2009
DOI: 10.1371/journal.pone.0006169
|View full text |Cite|
|
Sign up to set email alerts
|

A Model of Postural Control in Quiet Standing: Robust Compensation of Delay-Induced Instability Using Intermittent Activation of Feedback Control

Abstract: The main purpose of this study is to compare two different feedback controllers for the stabilization of quiet standing in humans, taking into account that the intrinsic ankle stiffness is insufficient and that there is a large delay inducing instability in the feedback loop: 1) a standard linear, continuous-time PD controller and 2) an intermittent PD controller characterized by a switching function defined in the phase plane, with or without a dead zone around the nominal equilibrium state. The stability ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
397
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(429 citation statements)
references
References 36 publications
19
397
1
1
Order By: Relevance
“…The second relies on the observation that the interplay between time delays and noisy perturbations can transiently stabilize an unstable fixed-point [12,14,15,68,71]. The third strategy is a nonlinear-type of control mechanism which relies on the properties of a saddle point [10,4]. The analytical explanation for transient stabilizations shown in Figure 12 is not presently known.…”
Section: Transient Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The second relies on the observation that the interplay between time delays and noisy perturbations can transiently stabilize an unstable fixed-point [12,14,15,68,71]. The third strategy is a nonlinear-type of control mechanism which relies on the properties of a saddle point [10,4]. The analytical explanation for transient stabilizations shown in Figure 12 is not presently known.…”
Section: Transient Stabilizationmentioning
confidence: 99%
“…Two general types of explanations have been advanced. First, it is possible that the intermittency may be event-driven, namely corrective forces are generated whenever the controlled variable crosses a threshold [4,10,12,33,34,39,68,69,71]. A well known example of threshold crossing in human balance control is the "safety-net" character of the ankle-hip-step control strategy used by humans to maintain balance in the face of increasingly large perturbations [18,86].…”
Section: Introductionmentioning
confidence: 99%
“…Intermittency is characterised by sub-movements which are triggered by an error crossing a threshold (Asai et al 2009;Hanneton et al 1997;Miall et al 1993;Wolpert et al 1992). In both self-selected and fast speed conditions, the weak correlations observed between the peak velocity and the constant error suggested that the young adults used adjustments to reach the endpoint position (Messier and Kalaska 1999).…”
Section: Continuous Vs Intermittent Modelsmentioning
confidence: 99%
“…The model we propose is similar to the one studied in Asai et al [25]-the PD control is switched on or off depending on the value of state variables. The model studied in Asai et al [25] is an extension of the studies conducted in Bottaro et al [26,27] where the authors introduce intermittently switched on/off controller that allows for a bounded motion, and it is this type of control which Asai et al [25] propose as the possible explanation for the sway motion during quiet standing. In the study of Asai et al [25], it is also shown that the bounded dynamics is linked with a motion along the stable manifold of a saddle point.…”
Section: Introductionmentioning
confidence: 99%